Loss of Sensitivity to Rewards by Dopamine Neurons May Underlie Age-Related Increased Probability Discounting - Tryon, Valerie L.; Baker, Phillip M.; Long, Jeffrey M.; Rapp, Peter R.; Mizumori, Sheri J. Y. (Frontiers in Aging Neuroscience, 2020)
Normative aging is known to affect how decisions are made in risky situations. Although important individual variability exists, on average, aging is accompanied by greater risk aversion. Here the behavioral and neural mechanisms of greater risk aversion were examined in young and old rats trained on an instrumental probability discounting task. Consistent with the literature, old rats showed greater discounting of reward value when the probability of obtaining rewards dropped below 100%. Behaviorally, reward magnitude discrimination was the same between young and old rats, and yet these same rats exhibited reduced sensitivity to positive, but not negative, choice outcomes. The latter behavioral result was congruent with additional findings that the aged ventral tegmental neurons (including dopamine cells) were less responsive to rewards when compared to the same cell types recorded from young animals. In sum, it appears that reduced responses of dopamine neurons to rewards contribute to aging-related changes in risky decisions.